Peningkatan Ekologi Lahan di Universitas Negeri Malang melalui Rating tool Greenship Kawasan - Yohanes Wilasa Widodo; Apif Miptahul Hajji; Dian Ariestadi (Dampak, 2021)
The environment is a place to carry out life, activities and providers of important elements such as oxygen, water and food. As a result of poor environmental quality such as temperature that is too high, low humidity and air pollution, it makes the living and working environment uncomfortable. Green Building Council Indonesia published Greenship Neighborhood that can be a reference in implentation of sustainable area. The components of land ecological enhancement consist of green open space, micro climate, land revitalization, flora and fauna. The area of State University of Malang (UM) with a total area of 416,203 m² becomes a small city that affects users of the area or the surrounding area. UM through the rating tool greenship area has very good land ecological quality. The green basic area with 28.12% fulfills the prerequisites, and the green area for the public is categorized as sufficient with 28.12% of the area. Very good habitat conservation by fulfilling the aspects of maintaining 95.84% of the area's large trees, using 99.385% of provincial local plants, and reforestation. Land revitalization is still in the sufficient category with 60% have been done. The microclimate aspect is categorized as very good with the lowest temperature isotherm in the area and efforts to apply it are carried out in all public areas of the area. Productive land area is categorized as very good with the dominance of 50% of production plant species spread over the entire area and the availability of special production land Keywords: Green Area, Campus, Greenship, Sustainability ABSTRAK Lingkungan adalah tempat untuk menjalani kehidupan, aktivitas, dan penyedia elemen penting seperti oksigen, air, dan makanan. Akibat kualitas lingkungan yang buruk, seperti suhu yang terlalu tinggi, kelembaban rendah, dan polusi udara, membuat lingkungan tempat hidup dan bekerja menjadi tidak nyaman. Green Building Council Indonesia menerbitkan Greenship Neighborhood yang dapat menjadi referensi dalam pelaksanaan area berkelanjutan. Komponen peningkatan ekologi tanah terdiri dari ruang terbuka hijau, iklim mikro, revitalisasi tanah, flora, dan fauna. Area Universitas Negeri Malang (UM) dengan luas total 416.203 m² menjadi sebuah kota kecil yang memengaruhi pengguna area atau area sekitarnya. UM melalui alat penilaian area greenship memiliki kualitas ekologi tanah yang sangat baik. Luas area dasar hijau sebesar 28,12% memenuhi persyaratan, dan area hijau untuk masyarakat dikategorikan sebagai cukup dengan 28,12% dari area tersebut. Konservasi habitat yang sangat baik dengan memenuhi aspek mempertahankan 95,84% dari pohon besar area tersebut, menggunakan 99,385% tanaman lokal provinsi, dan program penghijauan. Revitalisasi tanah masih dalam kategori cukup dengan 60% telah dilakukan. Aspek iklim mikro dikategorikan sebagai sangat baik dengan isoterma suhu terendah di area tersebut, dan upaya untuk menerapkannya dilakukan di semua area publik area tersebut. Luas tanah produktif dikategorikan sebagai sangat baik dengan dominasi 50% spesies tanaman produksi tersebar di seluruh area dan ketersediaan lahan produksi khusus. Kata Kunci: Kawasan hijau, Kampus, Greenship, Keberlanjutan